The Role Of Empowering Employers In Achieving Management Creativity In Islamic Banks In Lattakia Governorate. - قاسم سامر; الدالي ندى (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research paper aims to evaluate the effectiveness of administrative empowerment, which is used in Islamic banks in Lattakia governorate, through based on an evaluation of three main dimensions on which the effectiveness of empowerment is built, namely: delegation of authority, effective communication, motivating employees. The researcher has tested her hypotheses by analyzing the primary data collected by means of a questionnaire, which were distributed to a soft sample of human resources workers (34) singles, the value of the Alpha Cronbach coefficient exceeded (0.858), the researcher used in her statistical the Pearson correlation coefficient with the help of SPSS Statistical Edition / 25 /, The results were as follows: Effective communication as a dimension of empowering workers contributes to achieving one of the dimensions of administrative creativity in a weak way, and delegating authority and motivating workers does not contribute to achieving administrative creativity in the banks under study.